Negative association between testosterone concentration and inflammatory markers in young men: a nested cross-sectional study. - Johannes Bobjer (Public Library of Science (PLoS), 2013)
Objective Low grade systemic inflammation (LGSI) as well as androgen deficiency has in older men been associated with several pathologies, including cardiovascular disease (CVD). We wanted to investigate whether low testosterone levels are linked to biomarkers of LGSI already in young age, before any concurrent manifestations of CVD or other systemic diseases. Design Nested cross-sectional study. Methods Forty subfertile biochemically hypogonadal (n = 20) or eugonadal (n = 20) men (mean age 37 years, SD = 4.3) and 20 age-matched controls were randomly selected from an ongoing study on male subfertility. Subjects comprised male partners in infertile couples in whom also subnormal sperm concentration was present. Blood sampling, interviews, and anthropometric measures were undertaken. Serum levels of testosterone, LH, estradiol, SHBG, and 21 LGSI-markers were assessed. Results Among 21 inflammatory markers, macrophage inflammatory protein 1-alpha (MIP1a) (ß = -0.025; p = 0.028), 1-beta (MIP1B) (ß = -0.015; p = 0.049) and tumor necrosis factor alpha (TNFa) (ß = -0.015; p = 0.040) showed negative association to total testosterone (TT) levels. MIP1a (ß = -1.95; p = 0.001) and TNFa (ß = -0.95; p = 0.014) showed negative association to calculated free testosterone (cFT) levels. Compared to men with normal TT and cFT levels, TNFa levels were higher in men with subnormal levels of TT (mean ratio 1.61; p = 0.006) and cFT (mean ratio 1.58; p = 0.007). Also, MIP1a levels were higher in men with subnormal levels of TT (mean ratio 1.84; p = 0.030). Conclusions Subnormal testosterone may already in young age associate to LGSI, which might be a part of the mechanism underlying adverse health outcomes of male hypogonadism.